"Just Like Riding a Bike": A Model Matching Approach to Predicting the Enjoyment of a Cycling Exergame Experience. Issue 3 (3rd July 2018) - McGloin, Rory; Embacher, Kimberly
ABSTRACT: Innovations in technology have led to the introduction of exercise devices that feature interactive virtual worlds, often referred to as exergames. Using the theory of model matching, this study seeks to determine if controller naturalness and perceived realism are predictors of immersion in an exercise-based virtual environment and, in turn, if perceived immersion is a predictor of enjoyment of this exercise experience. Participants rode a 3-mile virtual course on an Expresso HD upright bicycle and then reported their attitudes toward the experience. Findings suggest that extending the theory of mental models from traditional video game play to the study of certain exergame-based technologies is an appropriate application of the theory. Additionally, given the influence of immersion on the overall enjoyment of the fitness experience identified in this study, these findings also have implications for the development and use of exergames that are immersive, realistic, and utilize naturalistic controllers to promote commitment to physical activity.